Sikap Belajar, Kebiasaan Belajar dan Motivasi Berprestasi Terhadap Prestasi Belajar - Fadli, Ibnul (‎‎‎TAZKIYA Journal of Psychology, 2019)
The purpose of this research is to understand the influence of learning attitude, habit of learning and achievement motivation against student’s performance on research methodology course. This study used a quantitative approach by involving 139 students of the faculty of psychology syarif hidayatullah state islamic university. Data was collected using questionnaire and being analyzed with multiple regression. The research results show that there is a significant impact (18,2%) between learning attitude, the habit of learning and achievements motivation against student’s performance on research methodology course.